Virtual reality–guided mindfulness for chronic pain in cancer survivors: protocol for the virtual mind study—a single-group feasibility trial - Baydoun, Mohamad; Gajtani, Zen; Patton, Michaela; McLennan, Andrew; Cartwright, Stephen; Carlson, Linda E. (Frontiers in Pain Research, 2024)
Background: Chronic cancer-related pain (CRP) can have a significant negative impact on quality of life. Mindfulness is hypothesized to mitigate chronic CRP by regulating both physical and emotional resistance to pain. In recent years, there has been interest in the use of virtual reality (VR) to deliver mindfulness meditation. VR provides an immersive and engaging environment, which may enhance one's focused attention to present-moment experiences, potentially making mindfulness less effortful and more efficacious for individuals with chronic pain. There has been little research in this area for people with a history of cancer.Objective: The aim of this mixed methods study is to evaluate the feasibility of a VR-guided mindfulness (VRGM) intervention offered to adult cancer survivors with chronic CRP.Methods: This mixed methods feasibility study will employ a single-arm, pretest-posttest design with semistructured interviews. In total, 15 cancer survivors will be enrolled in a 6-week home-based intervention that consists of 10-15 minutes of daily VRGM practice. The primary outcome is feasibility as assessed by accrual rates, retention in the study, intervention adherence, questionnaire completion, and side effect rates. Participants will be assessed on psychosocial outcome measures (ie, pain, sleep, depressive and anxiety symptoms, fatigue, quality of life, and mindfulness) before and after the intervention, and 6 weeks post intervention (follow-up). Changes in pain will be described in relation to levels of immersion and presence in the virtual environment, trait mindfulness, and amount of VRGM practice. Qualitative information will provide subjective detail on participants' experience with VRGM to complement quantitative data. This study has been approved by the Health Research Ethics Board of Alberta Cancer Committee (HREBA. .This novel intervention provides a potential alternative treatment to pharmacological pain management. Results from this study may inform future larger VGRM trials for chronic CRP to help reduce suffering in people with cancer. Study findings will be disseminated through open access publications, traditional conference presentations, professional cancer organizations, and social media platforms.